USING INTERACTIVE TECHNIQUES IN THE COURSE OF THE LESSON THROUGH FORMS - Nuriddinova Mohlaroyim Shavkatjon Qizi (Journals Park Publishing, 2023)
This article will talk about interactive methods used by students using forms to improve the effectiveness of the lesson in the course processes, through which an innovative approach to the educational system will be highlighted.
Keywords: forms, lesson efficiency, interactive methods, educational system, innovation